A New Entrepreneurial Decision-Making Support Framework for Assessing Business Line Correlations - Mircea Fulea; Gabriela Șandru; Stelian Brad; Mihaela Maftei (Amfiteatru Economic Journal, 2015)
Sustainability is probably the ultimate goal of any entrepreneur when initiating or developing a business. As it involves competitiveness, companies aim to produce differentiated economic offerings by reusing and sharing processes, components, information and knowledge - many times from different domains. However, to be effective, this should be envisaged already when developing the entrepreneurial plan or when assessing the opportunity of extending the business – therefore the need for planning / implementing / integrating several business lines (from various domains). As many of them may look attractive, an effective decision of starting one business line or another should be supported by some tool that allows a systematic assessment of the opportunity of implementing them. This paper proposes an algorithm that supports entrepreneurs in this respect. The opportunity of developing new business lines is assessed by estimating the mutual impact between them and existing business lines, their impact on organizational performance, and additional indicators such as financial effort, the estimated return on investment, technical and organizational difficulty, risk level or domain financing opportunities. An application example is presented in which an SME in an interdisciplinary domain (covering IT and life-sciences) assesses the opportunity of opening two new business lines.
Keywords: O20; O22; O30; 330; diversification strategies; business lines; support framework; SMEs